ORGANIZATIONAL DYNAMICS OF COMMUNITIES FOR WATER USERS (Case in Cihea Irrigation Area, Ciranjang District, Cianjur Regency, West Java) - Yayat Sukayat (Sosiohumaniora, 2020)
Growth in food demand caused by population growth exceeded food growth, encouraging the development of irrigation in the colonial era to the present. The solution offered is to intensify agriculture, along with the emergence of new varieties that are responsive to water, and fertilizer, in such a way that production goes up. Therefore water management at the farm level is very much needed. In the Cihea irrigation area, irrigation management (its management authority) has been handed over to farmers, starting from the Submission of Small Irrigation (PIK) program, PKPI (Renewal of Irrigation Management Policy) and WISMP (Water Resource and Irrigation Sector Management Program). Of the 90 P3As that are still developing, only 10% are still running. The non-functioning of the P3A still seems to be a problem in the process of institutionalization of P3A. The purpose of this study is to obtain an overview of the organization’s movements. This research is a quantitative study, with descriptive survey techniques. From the results of the study, P3A Titaguna is a dynamic P3A, because it is supported by a philosophy that prioritizes togetherness, structurally the highest decision is on the members, and in the process of coordination and clarification is prioritized.